Growth hormone/insulin-like growth factor I axis in health and disease states: an update on the role of intra-portal insulin - Yuen, Kevin C. J.; Hjortebjerg, Rikke; Ganeshalingam, Ashok Ainkaran; Clemmons, David R.; Frystyk, Jan (Frontiers in Endocrinology, 2024)
Growth hormone (GH) is the key regulator of insulin-like growth factor I (IGF-I) generation in healthy states. However, portal insulin delivery is also an essential co-player in the regulation of the GH/IGF-I axis by affecting and regulating hepatic GH receptor synthesis, and subsequently altering hepatic GH sensitivity and IGF-I generation. Disease states of GH excess (e.g., acromegaly) and GH deficiency (e.g., congenital isolated GH deficiency) are characterized by increased and decreased GH, IGF-I and insulin levels, respectively, where the GH/IGF-I relationship is reflected by a “primary association”. When intra-portal insulin levels are increased (e.g., obesity, Cushing’s syndrome, or due to treatment with glucocorticoids and glucagon-like peptide 1 receptor agonists) or decreased (e.g., malnutrition, anorexia nervosa and type 1 diabetes mellitus), these changes secondarily alter hepatic GH sensitivity resulting in a “secondary association” with discordant GH and IGF-I levels (e.g., high GH/low IGF-I levels or low GH/high IGF-I levels, respectively). Additionally, intra-portal insulin regulates hepatic secretion of IGFBP-1, an inhibitor of IGF-I action. Through its effects on IGFBP-1 and subsequently free IGF-I, intra-portal insulin exerts its effects to influence endogenous GH secretion via the negative feedback loop. Therefore, it is important to understand the effects of changes in intra-portal insulin when interpreting the GH/IGF-I axis in disease states. This review summarizes our current understanding of how changes in intra-portal insulin delivery to the liver in health, disease states and drug therapy use and misuse that leads to alterations in GH/IGF-I secretion that may dictate management decisions in afflicted patients.